2021
DOI: 10.4103/jpbs.jpbs_559_20
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge and Awareness of Medical Emergencies and Management among Dental Students

Abstract: Background: Every dentist should anticipate being confronted with a medical emergency (ME), and one should always be ready to treat the most catastrophic ones. Aim: This study aimed to assess the knowledge of dental clinical students of Tamil Nadu in the ME understanding and management to create awareness toward patient care. Methodology: A total of 768 dental students, including final-year students and residents from different colleges, took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
8
0
3
Order By: Relevance
“…Mohideen et al [ 39 ] evaluated the knowledge of dental students about medical emergencies and management. The majority of the authors’ queries were about cardiac parameters, such as knowledge about antihypertensive drugs or CVD drug interactions with local dental anesthetics such as lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Mohideen et al [ 39 ] evaluated the knowledge of dental students about medical emergencies and management. The majority of the authors’ queries were about cardiac parameters, such as knowledge about antihypertensive drugs or CVD drug interactions with local dental anesthetics such as lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…It requires immediate management as some can lead to dire consequences, and stabilization of the patient is needed till the patient recovers or is transferred to a hospital. It should be noted that most common medical emergencies do not proceed to the life-threatening condition of the patient if handled well and in time however any delay or incompetency in such situations can progress to serious consequences and can even lead to death (2). This not only results in the loss of a life that could have been prevented but can also lead to legal consequences for the practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Jordan found that social media are also one of the main resources to get information regarding COVID-19. 6 Several previous studies have discussed COVID-19 literacy in various countries and communities 6 7 8 9 as well as emergency situations such as literacy in medical emergency situations among dental students 10 11 and knowledge of dental trauma or emergencies from nondental communities. 12 13 None of the above studies discussed COVID-19 and dental emergencies simultaneously with educational video interventions.…”
Section: Introductionmentioning
confidence: 99%